Developing a Serial Search Task to Evaluate Procedural Memory and Investigating the Relationship Between Procedural Memory and Grammar in Farsi-speaking Children: A Preliminary Study. - Malekian, Maryam; Kazemi, Yalda; Ahmadi, Akram; Zarifian, Talieh (Archives of Rehabilitation, 2023)
Objective Procedural memory is a key component of long-term memory that can be assessed in different modalities, such as verbal and motor. Learning through procedural memory occurs in three stages: initial learning, consolidation, and retention. Several tasks evaluate procedural memory, but none have concurrently studied procedural learning in various modalities and learning stages. Besides, according to the declarative-procedural model, there may be an association between the performance of individuals in procedural learning and their state of the grammar of a language. Therefore, this study aimed to design a Serial Search Task (SST) for the simultaneous evaluation of procedural memory in motor and verbal modalities during three stages of learning and determine its reliability. Moreover, the relationship between procedural memory and grammar skills was examined. Materials & Methods This study is methodological research in the first stage and descriptive analytics in the second stage. First, based on the literature review and the opinions of three speech-language pathologists, some words with appropriate psycholinguistic features were chosen from the Persian picture naming set. Then, corresponding pictures were determined. The task was designed using Java programming language. The face validity of the task was evaluated, then after revisions, the reliability was determined. Face validity was assessed in 10 normal children, and the test-retest reliability was evaluated in 15 normal children aged 7-9 years; all of them were chosen using the convenience sampling method. In the second stage, to assess the relationship between grammatical skills and the SST, 20 normal children aged 7-9 years were selected by a mixed sampling method. Every child had exposed to a verbal modality in three stages: initial learning, consolidation (24 hours later), and retention (one week later). Then the same stages were performed in the motor modality. Each child's language skills were determined using the test of language development-primary (TOLD-P3), and the relationship between the two skills was determined. Statistical methods included the Pearson and Spearman correlation coefficients and repeated measures analysis of variance. Results The correlation values between two performances in the initial learning stage for the reaction time variable in verbal (r=0.84, P<0.001) and motor (r=0.80, P˂0.001) modalities and the variable of response accuracy in verbal (r=0.81, P=0.011) and motor (r=0.77, P=0.026) modalities were obtained. In the consolidation and retention stages, the correlation values for the reaction time variable in verbal (r=0.737, P=0.002) and motor (r=0.743, P=0.001) modalities and the variable of response accuracy in verbal (r=0.624, P=0.013) and motor (r=0.916, P<0.001) modalities were obtained. The relationship between grammar and procedural learning in the verbal modality was significant in the consolidation stage (P=0.045, CI:0.016-0.797, r=0.491). Conclusion SST is a reliable task to assess different stages of procedural memory in both verbal and motor modalities. Therefore, this task can be used to evaluate procedural memory in normal children aged 7-9 years. The current study's findings confirmed the predictions made by the declarative-procedural model during the consolidation stage in the verbal modality.